זהות במבחן: יהודה בורלא בין הוויי ספרדי להוויה ציונית - שמעוני בתיה (מכאן, 2007)
The writer Yehuda Burla is mostly known as an authentic portrayer of Sephardi Jewish life in Jerusalem and the Near Eastern countries during the first half of the 20th century. But his extensive work also includes the story of his hybrid identity, moving between two poles: the rooted Sephardic manner of life and the new being of the Zionist Aliyah. This movement to and fro between two worlds is a main key to Burla’s fiction. From his first novel Luna, his progress in Hebrew literature was marked with mixed feelings: the desire to be a part of the literary group that consisted of Ashkenazi and Zionist writers, and the fear of being rejected by this very group. In the article, I trace the development of Burla’s fiction and how it reflects the problematic encounter between the cultural dominant and the other, the native who came from the marginal culture. The first novels of Burla described in detailed way the life of the Sephardic groups in Jerusalem. The readers, both from the old and the new Yeshuv, embraced his literature. The newcomers saw the world he wrote about as an exotic and fascinating world. The critics accepted his work and marked out his natural talent as a storyteller. In his next books Burla became critical about the manners of the society he described, his own society. The more accepted he was by the dominant group, he became more judicial towards the Sephardic beliefs, manners etc. Later on his work was changed radically, and he represented the “Old Yeshuv” as a negative and stagnate world, that should be replaced by the new idealistic world. But although the massage was very clear on the overt level of the stories, a closer reading reveals a different meaning of them. The article suggests a new look on Burla’s relationship with the Zionistic dominant group, and shows the literary ways by which he accept the new ways of life and reject them at the same time.